Tunneling oxidation passivation contact solar cell and preparation method thereof
By using an ultraviolet-resistant aluminum oxide film layer and silicon nitride layer in tunneled oxidation passivation contact solar cells, the problem of premature degradation of the battery under ultraviolet radiation is solved, and the effect of significantly reducing the UV attenuation rate and extending the battery life is achieved.
Patent Information
- Application Number
- CN202411741464.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-11
AI Technical Summary
Existing tunneling oxidation passivation contact solar cells are prone to premature degradation under ultraviolet radiation, especially in large-scale mass production, and attenuation mechanisms that have not yet been fully identified and controlled may exist.
The ultraviolet-resistant alumina film layer was prepared by tube or plate atomic layer deposition technology. The film layer thickness was controlled between 4nm-20nm and the uniformity was controlled within 10%. A silicon nitride layer was added to the film layer to enhance the passivation effect.
Effectively prevent ultraviolet penetration, significantly reduce the UV attenuation rate, reduce it to less than -1%, extend the battery's service life and improve its UV resistance.
Smart Images

Figure CN119816000A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of solar cells, and in particular, to a tunneling oxidation passivation contact solar cell and a preparation method thereof. Background Art
[0002] Tunneling oxide passivated contact solar cells (TOPCon cells) have been shown to be insensitive to light-induced degradation (LID) and light-thermal-induced degradation (LeTID). Based on these performance advantages, modules with tunneling oxide passivated contact solar cells have rapidly increased their market share in recent years. However, emerging photovoltaic cell technologies always have potential risks, and there is the possibility of undiscovered degradation mechanisms during large-scale mass production. The Renewable Energy Testing Center (RETC) of the United States mentioned in its recent study "PV Module Index 2022" that cells manufactured using TOPCon technology may be at risk of premature degradation due to the influence of ultraviolet (UV) radiation.
[0003] Therefore, it is particularly important to develop a tunneling oxide passivated contact solar cell that can effectively resist UV attenuation. Summary of the invention
[0004] The present application aims to solve at least one of the technical problems existing in the prior art to at least a certain extent.
[0005] Therefore, in the first aspect of the present application, the present application proposes a tunneling oxide passivation contact solar cell. According to an embodiment of the present application, the tunneling oxide passivation contact solar cell includes an anti-ultraviolet aluminum oxide film layer, the thickness of the anti-ultraviolet aluminum oxide film layer is 4nm-20nm, and the thickness uniformity is less than or equal to 10%. Therefore, the tunneling oxide passivation contact solar cell of the present application has good UV resistance, can effectively prevent ultraviolet rays from penetrating, and has an anti-UV attenuation effect, reducing its UV attenuation to within -1%.
[0006] According to an embodiment of the present application, the tunneling oxide passivation contact solar cell further includes at least one of the following additional technical features:
[0007] According to an embodiment of the present application, the anti-ultraviolet aluminum oxide film layer is prepared by tubular atomic layer deposition, and the thickness of the anti-ultraviolet aluminum oxide film layer is 4nm-6nm. Therefore, by adopting tubular atomic layer deposition to prepare the anti-ultraviolet aluminum oxide film layer, the thickness of the anti-ultraviolet aluminum oxide film layer is within the above range, which can make the prepared anti-ultraviolet aluminum oxide film layer more uniform and dense, and have better passivation effect and anti-ultraviolet effect.
[0008] According to an embodiment of the present application, the anti-ultraviolet aluminum oxide film layer is prepared by plate-type atomic layer deposition, and the thickness of the anti-ultraviolet aluminum oxide film layer is 8nm-15nm. Therefore, by adopting plate-type atomic layer deposition to prepare the anti-ultraviolet aluminum oxide film layer, the thickness of the anti-ultraviolet aluminum oxide film layer is within the above range, which can make the prepared anti-ultraviolet aluminum oxide film layer more uniform and dense, and at the same time have better passivation effect and anti-ultraviolet effect.
[0009] According to an embodiment of the present application, the anti-ultraviolet aluminum oxide film layer satisfies one of the following conditions:
[0010] A. The anti-ultraviolet aluminum oxide film layer comprises a first aluminum oxide film layer and a second aluminum oxide film layer stacked in sequence, wherein the first aluminum oxide film layer is prepared by atomic layer deposition, and the second aluminum oxide film layer is prepared by chemical vapor deposition, wherein the thickness of the first aluminum oxide film layer is greater than or equal to 4 nm, and the thickness of the second aluminum oxide film layer is 3 nm-8 nm;
[0011] B. The anti-ultraviolet aluminum oxide film layer comprises a third aluminum oxide film layer and a fourth aluminum oxide film layer stacked in sequence, wherein the third aluminum oxide film layer is prepared by plasma enhanced atomic layer deposition, and the fourth aluminum oxide film layer is prepared by chemical vapor deposition, and the thickness of the third aluminum oxide film layer is greater than or equal to 4 nm, and the thickness of the fourth aluminum oxide film layer is 3 nm-8 nm;
[0012] C. The anti-ultraviolet aluminum oxide film layer includes a fifth aluminum oxide film layer, a sixth aluminum oxide film layer and a seventh aluminum oxide film layer which are stacked in sequence, the fifth aluminum oxide film layer is prepared by the atomic layer deposition, the sixth aluminum oxide film layer is prepared by the chemical vapor deposition, the seventh aluminum oxide film layer is prepared by the plasma enhanced atomic layer deposition, the thickness of the fifth aluminum oxide film layer is 1nm-3nm, the thickness of the sixth aluminum oxide film layer is 3nm-8nm, the thickness of the seventh aluminum oxide film layer is 1nm-5nm, and the sum of the thicknesses of the fifth aluminum oxide film layer and the seventh aluminum oxide film layer is greater than or equal to 4nm.
[0013] Therefore, by adopting the above-mentioned combination of multiple methods to prepare the UV-resistant aluminum oxide film layer, the film advantages of atomic layer deposition, the deposition rate of chemical vapor deposition, and the advantages of plasma enhanced atomic layer deposition that does not require heating and has little device damage can be combined, so that the uniformity and passivation effect of the prepared UV-resistant aluminum oxide film layer can be guaranteed; at the same time, it can effectively block ultraviolet rays, reduce damage to battery materials, and extend the service life of the battery.
[0014] According to an embodiment of the present application, the refractive index of the anti-ultraviolet aluminum oxide film layer prepared by the atomic layer deposition or the plasma enhanced atomic layer deposition is 1.62 to 1.68.
[0015] According to an embodiment of the present application, the battery further includes a silicon nitride layer, which is disposed on a surface of the anti-ultraviolet aluminum oxide film layer, wherein the silicon nitride layer satisfies at least one of the following conditions: the silicon-nitrogen ratio in the silicon nitride layer is 1:(3-5); the refractive index of the silicon nitride layer is 2.25-2.55. Thus, the silicon nitride layer can reduce the recombination of electrons and holes on the silicon surface, effectively reduce the surface density, thereby reducing the non-radiative recombination of carriers and enhancing its passivation effect; at the same time, the refractive index of the silicon nitride layer is within this range, which can reduce the chemical structure changes of the SiNx layer caused by ultraviolet light, such as the breakage of the Si-H bond, which leads to a decrease in the passivation effect.
[0016] In a second aspect of the present application, the present application proposes a method for preparing the tunneling oxide passivation contact solar cell described in the first aspect. According to an embodiment of the present application, the method for preparing the tunneling oxide passivation contact solar cell includes the step of preparing an anti-ultraviolet aluminum oxide film layer, and the method for preparing the anti-ultraviolet aluminum oxide film layer includes atomic layer deposition.
[0017] According to an embodiment of the present application, the method for preparing an anti-ultraviolet aluminum oxide film layer may further include at least one of the following additional technical features:
[0018] According to an embodiment of the present application, the anti-ultraviolet aluminum oxide film layer is prepared by tubular atomic layer deposition, and the steps include: 1) setting the chamber temperature of the tubular atomic layer deposition equipment to 260°C-290°C, and the process preheating time to 800s-1000s; 2) introducing water into the chamber, during which the pulse time is 5s-10s, the purge time is 10s-15s, the process flow rate is 15sccm-20sccm, and the number of cycles of the process is 3-7 times; 3) introducing trimethylaluminum and water into the chamber at the same time, during which the pulse time is 5s-10s, the purge time is 10s-15s, the process flow rate is 20sccm-25sccm, and the number of cycles of the process is 30-40 times. Thus, the anti-ultraviolet aluminum oxide film layer prepared by this method can have good uniformity, compactness and passivation, as well as anti-ultraviolet performance.
[0019] According to an embodiment of the present application, the anti-ultraviolet aluminum oxide film layer is prepared by plate-type atomic layer deposition, and the steps include: setting the chamber temperature of the plate-type atomic layer deposition equipment to 250°C-290°C, and simultaneously introducing trimethylaluminum and water into the chamber, in which the flow rate of the trimethylaluminum is 2200sccm-2400sccm, the flow rate of the water is 2000sccm-2300sccm, the pressure is 2mbar-4mbar, and the number of cycles of the process is 8-12 times. Thus, the anti-ultraviolet aluminum oxide film layer prepared by this method can have good uniformity, compactness and passivation, as well as anti-ultraviolet performance.
[0020] According to an embodiment of the present application, the anti-ultraviolet aluminum oxide film layer is prepared by the following method: firstly, a first aluminum oxide film layer is prepared by atomic layer deposition, and then a second aluminum oxide film layer is prepared by chemical vapor deposition on a surface of the first aluminum oxide film layer, wherein the atomic layer deposition step comprises: 1) setting the chamber temperature of the atomic layer deposition equipment to 260-290°C; 2) introducing water into the chamber, during which the flow rate of the water is 600sccm-1500sccm and the pressure is 1500mtorr-200 0mtorr, the introduction time is 5s-15s; 3) the first purge, the first purge time is 20s-30s; 4) the first vacuumization, the first vacuumization time is 25s-35s; 5) trimethylaluminum is introduced into the chamber, during which the flow rate of trimethylaluminum is 2300sccm-2700sccm, the pressure is 1500mtorr-2000mtorr, and the introduction time is 10s-20s; 6) the second purge, the second purge time is 20s-30s; 7) the second vacuumization, the The second vacuuming time is 25s-35s; the atomic layer deposition step 2)-step 7) is defined as a cycle, and the number of cycles is 10-15 times; the chemical vapor deposition step includes: 1) setting the chamber temperature of the chemical vapor deposition equipment to 240°C-290°C; 2) introducing N2O and trimethylaluminum into the chamber at the same time, in which the flow rate of N2O is 2000sccm-5000sccm, the flow rate of trimethylaluminum is 500sccm-1500sccm, and the pressure is 1500mtorr-2 000mtorr, the introduction time is 20s-40s; 3) the first deposition stage, during this stage, the flow rate of N2O is 2000sccm-5000sccm, the flow rate of trimethylaluminum is 500sccm-1500sccm, the pressure is 1500mtorr-2000mtorr, the power is 8000W-10000W, the pulse switch ratio is 1:700, and the first deposition time is 100s-150s; 4) the third vacuuming, the third vacuuming time is 25s-35s. Thus, the prepared anti-ultraviolet aluminum oxide film can have good uniformity, compactness and passivation, as well as anti-ultraviolet performance.
[0021] According to an embodiment of the present application, the anti-ultraviolet aluminum oxide film layer is prepared by the following method: first, a third aluminum oxide film layer is prepared by plasma enhanced atomic layer deposition, and then a fourth aluminum oxide film layer is prepared by chemical vapor deposition on a surface of the third aluminum oxide film layer, wherein the plasma enhanced atomic layer deposition step comprises: 1) setting the chamber temperature of the plasma enhanced atomic layer deposition equipment to 240°C-290°C; 2) introducing N2O and trimethylaluminum into the chamber, and during the process, the flow rate of N2O is 2000sccm-5000s ccm, the flow rate of trimethylaluminum is 500sccm-2000sccm, the pressure is 1500mtorr-2000mtorr, and the introduction time is 20s-40s; 3) the second deposition stage, during this stage, the flow rate of N2O is 2000sccm-5000sccm, the flow rate of trimethylaluminum is 500sccm-2000sccm, the pressure is 1500mtorr-2000mtorr, the power is 3000W-5000W, the pulse switching ratio is 1:700, and the second deposition time is 10s -20s; 4) fourth vacuuming, the fourth vacuuming time is 25s-35s; defining the steps 2)-4) of the plasma enhanced atomic layer deposition as a cycle, the number of cycles is 5-10 times; the chemical vapor deposition step comprises: 1) setting the chamber temperature of the chemical vapor deposition equipment to 240°C-290°C; 2) simultaneously introducing N2O and trimethylaluminum into the chamber, in which the flow rate of N2O is 2000sccm-5000sccm, the flow rate of trimethylaluminum is 500sccm-1500sccm, and the pressure is 1 500mtorr-2000mtorr, the introduction time is 20s-40s; 3) the first deposition stage, during this stage, the flow rate of N2O is 2000sccm-5000sccm, the flow rate of trimethylaluminum is 500sccm-1500sccm, the pressure is 1500mtorr-2000mtorr, the power is 8000W-10000W, the pulse switch ratio is 1:700, and the first deposition time is 100s-150s; 4) the third vacuuming, the third vacuuming time is 25s-35s. Thus, the method can make the prepared anti-ultraviolet aluminum oxide film have good uniformity, density and passivation, as well as anti-ultraviolet performance.
[0022] According to an embodiment of the present application, the anti-ultraviolet aluminum oxide film layer is prepared by the following method: first, a fifth aluminum oxide film layer is prepared by atomic layer deposition, and then a sixth aluminum oxide film layer is prepared by chemical vapor deposition on a surface of the fifth aluminum oxide film layer, and finally, a seventh aluminum oxide film layer is prepared by plasma enhanced atomic layer deposition on a surface of the sixth aluminum oxide film layer away from the fifth aluminum oxide film layer, wherein the atomic layer deposition step includes: 1) setting the chamber temperature of the atomic layer deposition equipment to 260-290°C; 2) introducing water into the chamber, during which the water flow rate is 600sccm-1500sccm and the pressure is 1500mtorr-2000m torr, the introduction time is 5s-15s; 3) the first purge, the first purge time is 20s-30s; 4) the first vacuum, the first vacuum time is 25s-35s; 5) trimethylaluminum is introduced into the chamber, during which the flow rate of trimethylaluminum is 2300sccm-2700sccm, the pressure is 1500mtorr-2000mtorr, and the introduction time is 10s-20s; 6) the second purge, the second purge time is 20s-30s; 7) the second vacuum, the second vacuum time is 25s-35s; the atomic layer deposition step 2)-step 7) is defined as a cycle, the number of cycles is 10-15 times; the chemical vapor phase The deposition steps include: 1) setting the chamber temperature of the chemical vapor deposition equipment to 240°C-290°C; 2) introducing N2O and trimethylaluminum into the chamber at the same time, during which the flow rate of N2O is 2000sccm-5000sccm, the flow rate of trimethylaluminum is 500sccm-1500sccm, the pressure is 1500mtorr-2000mtorr, and the introduction time is 20s-40s; 3) a first deposition stage, during which the flow rate of N2O is 2000sccm-5000sccm, the flow rate of trimethylaluminum is 500sccm-1500sccm, the pressure is 1500mtorr-2000mtorr, and the introduction time is 20s-40s. torr, the power is 8000W-10000W, the pulse switch ratio is 1:700, and the first deposition time is 100s-150s; 4) the third vacuum pumping, the third vacuum pumping time is 25s-35s; the plasma enhanced atomic layer deposition step includes: 1) setting the chamber temperature of the plasma enhanced atomic layer deposition equipment to 240℃-290℃; 2) introducing N2O and trimethylaluminum into the chamber, in this process, the flow rate of N2O is 2000sccm-5000sccm, the flow rate of trimethylaluminum is 500sccm-2000sccm, the pressure is 1500mtorr-2000mtorr, and the introduction time is 20s-40s;3) The second deposition stage, during which the flow rate of N2O is 2000sccm-5000sccm, the flow rate of trimethylaluminum is 500sccm-2000sccm, the pressure is 1500mtorr-2000mtorr, the power is 3000W-5000W, the pulse on-off ratio is 1:700, and the second deposition time is 10-20s; 4) The fourth vacuum pumping, the fourth vacuum pumping time is 25-35s; the steps 2)-4) of the plasma enhanced atomic layer deposition are defined as a cycle, and the number of cycles is 5-10 times; thus, the prepared anti-ultraviolet aluminum oxide film can have good uniformity, compactness and passivation, as well as anti-ultraviolet performance. ;
[0023] According to an embodiment of the present application, the method further includes the step of preparing a silicon nitride layer on a surface of the anti-ultraviolet aluminum oxide film layer.
[0024] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0026] Figure 1 is a flow chart of preparing an anti-ultraviolet aluminum oxide film layer by using tubular atomic layer deposition according to an embodiment of the present application;
[0027] Figure 2 is a flow chart of preparing an anti-ultraviolet aluminum oxide film layer by plate-type atomic layer deposition according to an embodiment of the present application;
[0028] Figure 3 is a flow chart of preparing a first aluminum oxide film layer by atomic layer deposition according to an embodiment of the present application;
[0029] Figure 4 is a flow chart of preparing a second aluminum oxide film layer by chemical vapor deposition according to an embodiment of the present application;
[0030] Figure 5 This is a flow chart of preparing a third aluminum oxide film layer by plasma enhanced atomic layer deposition according to an embodiment of the present application. DETAILED DESCRIPTION
[0031] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0032] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0034] In this document, the terms "include" or "comprising" are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0035] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.
[0036] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0037] Although some measures have been taken to enhance the UV resistance of batteries during mass production, these measures are mainly limited to improving the passivation film on the front and back of the battery. However, the existing passivation process is still relatively broad in terms of process settings and quality monitoring, lacking specificity and precision.
[0038] Specifically, current research has not yet deeply explored and identified the core factors that affect the anti-UV performance of batteries, nor has it formed a systematic management and control method to effectively guide production practices. This has led to a relatively high attenuation rate of batteries under ultraviolet irradiation, usually between -3% and -5%, which not only increases the risk of premature degradation of batteries and photovoltaic modules, but also has an adverse effect on their overall quality assurance and performance. Therefore, in order to promote the continuous advancement of battery technology and meet the growing market demand, it is urgent to conduct more in-depth research and innovation on the anti-UV performance of batteries. This includes but is not limited to the development of new anti-UV materials, optimization of the preparation process of the passivation layer, establishment of a more precise quality monitoring system, and exploration of more effective battery design and packaging technology. Through these measures, the anti-UV performance of batteries can be significantly improved, their service life can be extended, and their stability and reliability under various environmental conditions can be ensured.
[0039] After a large number of experiments, the applicant found that the core factor for the anti-UV ability of the tunneling oxide passivation contact solar cell end is the aluminum oxide film layer, and the thickness and uniformity of the aluminum oxide film layer directly affect the anti-UV performance of the battery. By precisely controlling these parameters, the durability and reliability of the battery can be significantly improved, and the performance degradation caused by ultraviolet rays can be reduced. In order to enable the battery to effectively resist UV attenuation and reduce its UV attenuation to less than -1%, the applicant has conducted a lot of research on the preparation method of aluminum oxide and found that the film thickness of aluminum oxide prepared by different methods has different requirements. They will be introduced separately below.
[0040] Tunneling oxide passivated contact solar cells
[0041] In one aspect of the present application, the present application proposes a tunneling oxide passivation contact solar cell. According to an embodiment of the present application, the tunneling oxide passivation contact solar cell includes an anti-ultraviolet aluminum oxide film layer, the thickness of the anti-ultraviolet aluminum oxide film layer is 4nm-20nm, and the thickness uniformity is less than or equal to 10%. For example, the thickness of the anti-ultraviolet aluminum oxide film layer can be 4nm, 6nm, 8nm, 10nm, 12nm, 15nm, 17nm, 20nm, etc., or can be a range composed of any of the above values. For example, the thickness uniformity can be 1%, 2%, 4%, 5%, 8%, 10%, etc., respectively, or can be a range composed of any of the above values.
[0042] After a large number of experiments, the applicant found that ultraviolet light will cause changes in the chemical structure of the passivation layer on the surface of the battery (such as the breaking of Si-H bonds), which will lead to a decrease in the passivation effect, while aluminum oxide can enhance the thermal reflectivity, effectively prevent the recombination loss of photogenerated charges on the surface of the battery, and enhance the absorption of light. Therefore, the aluminum oxide film layer is a key factor in the UV resistance of the tunneling oxidation passivation contact solar cell, and the thickness and uniformity of the aluminum oxide film layer will affect the UV resistance of the battery. By setting the thickness and uniformity of the aluminum oxide film layer of the tunneling oxidation passivation contact solar cell within the above range, the UV resistance of aluminum oxide can be effectively improved, thereby improving the UV resistance of the tunneling oxidation passivation contact solar cell. Therefore, the tunneling oxidation passivation contact solar cell of the present application not only has a good passivation effect, but also has a good UV resistance, and can reduce UV attenuation to less than -1%.
[0043] It should be noted that thickness uniformity refers to the consistency of the thickness of the anti-UV aluminum oxide film layer at different measurement points within the same battery cell. Thickness uniformity = extreme difference in thickness of the anti-UV aluminum oxide film layer / average thickness / 2. The smaller the value, the better the thickness uniformity. In the process of preparing the anti-ultraviolet aluminum oxide film layer, the thickness uniformity of the prepared anti-ultraviolet aluminum oxide film layer can be judged by testing its intra-sheet uniformity, inter-sheet uniformity and inter-tube uniformity respectively. Specifically, "intra-sheet uniformity" refers to the consistency of the thickness and quality of the aluminum oxide film layer between different measurement points within the same battery cell. Intra-sheet uniformity = intra-sheet range / intra-sheet mean / 2. High intra-sheet uniformity means that the film layer is evenly distributed on the entire battery cell without local over-thickness or over-thinness, which contributes to the overall stability and consistency of battery performance; "inter-sheet uniformity" refers to the consistency of the aluminum oxide film layer between different battery cells in the same tube. Inter-sheet uniformity = all single-point ranges of the whole tube / the mean of the whole tube / 2; "inter-tube uniformity" refers to the consistency of the aluminum oxide film layer between battery cells prepared between different tubes. Inter-tube uniformity = all tube ranges / all tube mean / 2. Uniformity is intended to ensure that the film quality of each battery cell is the same in batch production, whether it is intra-sheet, inter-sheet or inter-tube, which is an important condition to ensure the uniformity and reliability of the final product performance.
[0044] In some embodiments of the present application, in the process of preparing the anti-ultraviolet aluminum oxide film layer, the intra-sheet uniformity, inter-sheet uniformity and inter-tube uniformity are respectively less than or equal to 10%. For example, the intra-sheet uniformity, inter-sheet uniformity and inter-tube uniformity can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., or can be a range composed of any of the above values. Therefore, by making the intra-sheet, inter-sheet and inter-tube uniformity within the above range, the aluminum oxide film layer in the overall battery cell can be made more uniform, which helps to improve the anti-ultraviolet performance of the battery.
[0045] In some embodiments of the present application, the anti-ultraviolet aluminum oxide film layer is prepared by tubular atomic layer deposition, and the thickness of the anti-ultraviolet aluminum oxide film layer is 4nm-6nm. For example, the thickness of the anti-ultraviolet aluminum oxide film layer can be 4nm, 5nm, 6nm, etc., or can be a range composed of any of the above numerical values. Therefore, tubular atomic layer deposition helps to achieve highly uniform deposition of the anti-ultraviolet aluminum oxide film layer, and the deposited anti-ultraviolet aluminum oxide film layer has high density and can serve as a good passivation layer; at the same time, controlling the thickness of the anti-ultraviolet aluminum oxide film layer within the above range can effectively prevent ultraviolet rays from penetrating, play a role in anti-UV attenuation, and thus enhance the anti-UV attenuation effect of the battery, while reducing the metal electrode from being able to burn through the aluminum oxide film layer and achieving ohmic contact, thereby affecting current collection and reducing the conversion efficiency of the battery.
[0046] In some embodiments of the present application, the anti-ultraviolet aluminum oxide film layer is prepared by tubular atomic layer deposition, the refractive index of the anti-ultraviolet aluminum oxide film layer is 1.62-1.68, and the thickness of the single-cycle anti-ultraviolet aluminum oxide film layer is 0.12nm-0.15nm. Therefore, the anti-ultraviolet aluminum oxide film layer can have the characteristics of high quality, dense and pinhole-free, and can effectively prevent ultraviolet rays from penetrating, thereby achieving the effect of anti-UV attenuation.
[0047] The "single-cycle aluminum oxide film thickness" mentioned in this application refers to the thickness of the aluminum oxide film layer deposited on the substrate after completing a complete reaction cycle.
[0048] In some embodiments of the present application, the anti-ultraviolet aluminum oxide film layer is prepared by plate-type atomic layer deposition, and the thickness of the anti-ultraviolet aluminum oxide film layer is 8nm-15nm. For example, the thickness of the anti-ultraviolet aluminum oxide film layer can be 8nm, 10nm, 12nm, 14nm, 15nm, etc., or can be a range composed of any of the above numerical values. Therefore, plate-type atomic layer deposition helps to achieve highly uniform deposition of anti-ultraviolet aluminum oxide film layers, and the deposited anti-ultraviolet aluminum oxide film layer has high density and can serve as a good passivation layer; at the same time, controlling the thickness of the anti-ultraviolet aluminum oxide film layer within the above range can effectively prevent ultraviolet rays from penetrating, play a role in anti-UV attenuation, and thus enhance the anti-UV attenuation effect of the battery, while reducing the metal electrode from being able to burn through the aluminum oxide film layer and achieving ohmic contact, thereby affecting current collection and reducing the conversion efficiency of the battery.
[0049] In some embodiments of the present application, the anti-ultraviolet aluminum oxide film layer satisfies the following conditions: the anti-ultraviolet aluminum oxide film layer comprises a first aluminum oxide film layer and a second aluminum oxide film layer stacked in sequence, the first aluminum oxide film layer is prepared by atomic layer deposition (ALD), the second aluminum oxide film layer is prepared by chemical vapor deposition (CVD), the thickness of the first aluminum oxide film layer is greater than or equal to 4nm, and the thickness of the second aluminum oxide film layer is 3nm-8nm. For example, the thickness of the first aluminum oxide film layer can be 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, etc., or can be a range composed of any of the above values. For example, the thickness of the second aluminum oxide film layer can be 3nm, 4nm, 5nm, 6nm, 7nm or 8nm, etc., or can be a range composed of any of the above values. Therefore, by adopting atomic layer deposition and chemical vapor deposition, the anti-ultraviolet aluminum oxide film layer can have better uniformity and density; at the same time, controlling the thickness of the first aluminum oxide film layer and the second aluminum oxide film layer within the above range can not only effectively prevent ultraviolet radiation from penetrating, play a role in anti-UV attenuation, and enhance the anti-UV attenuation effect of the battery, but also can enhance the passivation effect of the battery, making the battery more efficient.
[0050] In some embodiments of the present application, the refractive index of the first aluminum oxide film layer prepared by atomic layer deposition is 1.62-1.68, and the thickness of the single-cycle anti-ultraviolet aluminum oxide film layer is 0.12nm-0.15nm. Therefore, the anti-ultraviolet aluminum oxide film layer can have the characteristics of high quality, dense and pinhole-free, which can effectively prevent ultraviolet rays from penetrating, thereby achieving the effect of anti-UV attenuation.
[0051] In some embodiments of the present application, the anti-ultraviolet aluminum oxide film layer satisfies the following conditions: the anti-ultraviolet aluminum oxide film layer includes a third aluminum oxide film layer and a fourth aluminum oxide film layer stacked in sequence, the third aluminum oxide film layer is prepared by plasma enhanced atomic layer deposition (PEALD), the fourth aluminum oxide film layer is prepared by chemical vapor deposition, the thickness of the third aluminum oxide film layer is greater than or equal to 4nm, and the thickness of the fourth aluminum oxide film layer is 3nm-8nm. For example, the thickness of the third aluminum oxide film layer can be 4nm, 5nm, 6nm, 7nm or 8nm, etc., or can be a range composed of any of the above values. For example, the thickness of the fourth aluminum oxide film layer can be 3nm, 4nm, 5nm, 6nm, 7nm or 8nm, etc., or can be a range composed of any of the above values. Therefore, by adopting plasma enhanced atomic layer deposition and chemical vapor deposition, the anti-ultraviolet aluminum oxide film layer can have better uniformity and density; at the same time, controlling the thickness of the third aluminum oxide film layer and the fourth aluminum oxide film layer within the above range can not only effectively prevent ultraviolet radiation penetration, play a role in anti-UV attenuation, and enhance the anti-UV attenuation effect of the battery, but also enhance the passivation effect of the battery, thereby improving the efficiency of the battery.
[0052] In some embodiments of the present application, the anti-ultraviolet aluminum oxide film layer satisfies the following conditions: the anti-ultraviolet aluminum oxide film layer includes a fifth aluminum oxide film layer, a sixth aluminum oxide film layer and a seventh aluminum oxide film layer stacked in sequence, the fifth aluminum oxide film layer is prepared by the atomic layer deposition, the sixth aluminum oxide film layer is prepared by the chemical vapor deposition, the seventh aluminum oxide film layer is prepared by the plasma enhanced atomic layer deposition, the thickness of the fifth aluminum oxide film layer is 1nm-3nm, the thickness of the sixth aluminum oxide film layer is 3nm-8nm, and the thickness of the seventh aluminum oxide film layer is 1nm-5nm. For example, the thickness of the fifth aluminum oxide film layer can be 1nm, 2nm or 3nm, or can be a range composed of any of the above values. For example, the thickness of the sixth aluminum oxide film layer can be 3nm, 4nm, 5nm, 6nm, 7nm or 8nm, or can be a range composed of any of the above values. For example, the thickness of the seventh aluminum oxide film layer can be 1nm, 2nm, 3nm, 4nm or 5nm, or can be a range of any of the above values. Furthermore, the sum of the thicknesses of the fifth aluminum oxide film layer and the seventh aluminum oxide film layer is greater than or equal to 4nm. Therefore, by adopting atomic layer deposition, plasma enhanced atomic layer deposition and chemical vapor deposition, the advantages of the film layer of atomic layer deposition, the deposition rate of chemical vapor deposition, and the advantages of plasma enhanced atomic layer deposition that does not require heating and has little device damage can be combined, so that the uniformity, density and passivation effect of the prepared anti-ultraviolet aluminum oxide film layer can be guaranteed; at the same time, it can effectively block ultraviolet rays, reduce damage to battery materials, and extend the service life of the battery.
[0053] It should be noted that "atomic layer deposition (ALD)" refers to a method in which a substance can be plated layer by layer on the surface of a substrate in the form of a single atomic film. This method deposits only one layer of atoms in each reaction, so that the uniformity and thickness can be well controlled; the "tubular atomic layer deposition" described in this application refers to a method of performing atomic layer deposition using tubular ALD equipment similar to Microguide and Songyu; "plate atomic layer deposition" refers to a method of performing atomic layer deposition using equipment similar to Ideal ALD.
[0054] In some embodiments of the present application, the battery further comprises a silicon nitride layer, and the silicon nitride layer is disposed on a surface of the anti-ultraviolet aluminum oxide film layer, wherein the silicon nitride layer satisfies at least one of the following conditions: the silicon-nitrogen ratio in the silicon nitride layer is 1:(3-5); the refractive index of the silicon nitride layer is 2.25-2.55. Thus, by making the silicon-nitrogen ratio in the silicon nitride layer within the above range, the silicon nitride layer can reduce the recombination of electrons and holes on the silicon surface, effectively reduce the surface density, thereby reducing the non-radiative recombination of carriers and enhancing its passivation effect; by making the refractive index of the silicon nitride layer within the above range, the chemical structure change of the SiNx layer caused by ultraviolet light, such as the breaking of the Si-H bond, can be reduced, resulting in a decrease in the passivation effect.
[0055] For example, the silicon-nitrogen ratio may be 1:3, 1:4, 1:5, etc., or may be a range consisting of any of the above values.
[0056] For example, the refractive index of the silicon nitride layer may be 2.25, 2.3, 2.35, 2.4, 2.45, 2.5 or 2.55, or may be a range consisting of any of the above values.
[0057] Preparation method
[0058] In another aspect of the present application, the present application proposes a method for preparing the above-mentioned tunneling oxide passivation contact solar cell. According to an embodiment of the present application, the method for preparing the tunneling oxide passivation contact solar cell includes the step of preparing an anti-ultraviolet aluminum oxide film layer, and the method for preparing the anti-ultraviolet aluminum oxide film layer includes atomic layer deposition. As a result, the prepared anti-ultraviolet aluminum oxide film layer can have good uniformity and density, effectively prevent the recombination loss of photogenerated charges on the surface of the battery, enhance the absorption of light, and thus improve the anti-UV performance of the battery.
[0059] In some embodiments of the present application, the method for preparing an anti-ultraviolet aluminum oxide film layer may further include at least one of the following additional technical features:
[0060] In some embodiments of the present application, the anti-ultraviolet aluminum oxide film layer is prepared by tubular atomic layer deposition, referring to Figure 1 , the steps include:
[0061] S100: Setting the chamber temperature and process preheating time of tubular atomic layer deposition equipment
[0062] In this process, the chamber temperature of the tubular atomic layer deposition equipment is set to 260° C.-290° C., and the process preheating time of the tubular atomic layer deposition equipment is set to 800s-1000s. Thus, the formation of the UV-resistant aluminum oxide film layer can be promoted.
[0063] Illustratively, the cavity temperature may be 260° C., 270° C., 280° C., or 290° C., or may be a range consisting of any of the above values.
[0064] Illustratively, the process preheating time may be 800s, 850s, 900s, 950s or 1000s, etc., or may be a range consisting of any of the above numerical values.
[0065] In some embodiments of the present application, the tubular atomic layer deposition equipment may be tubular atomic layer deposition equipment similar to Microguide, Songyu, etc.
[0066] S200: Water is introduced into the cavity
[0067] In this process, water is introduced into the cavity of the tubular atomic layer deposition equipment, the pulse time is set to 5s-10s, the purge time is 10s-15s, the process flow rate is 15sccm-20sccm, and the number of cycles of this process is 3 to 7 times. Thus, by setting the above parameters within a specific range, the thickness of the prepared anti-ultraviolet aluminum oxide film can be within the range of 4nm-6nm, and the uniformity within the sheet, between sheets and between tubes is less than or equal to 10%, respectively, thereby improving the anti-ultraviolet effect of the battery.
[0068] Exemplarily, the pulse time may be 5s, 6s, 7s, 8s, 9s, 10s, etc., or may be a range consisting of any of the above values.
[0069] Exemplarily, the purge time may be 10 s, 11 s, 12 s, 13 s, 14 s, 15 s, etc., or may be a range consisting of any of the above values.
[0070] Illustratively, the process flow rate may be 15 sccm, 16 sccm, 17 sccm, 18 sccm, 19 sccm, 20 sccm, etc., or may be a range consisting of any of the above values.
[0071] Illustratively, the number of cycles can be 3, 4, 5, 6, 7, etc., or can be a range consisting of any of the above values.
[0072] S300: introducing trimethylaluminum and water into the cavity simultaneously
[0073] In this process, trimethylaluminum (TMA) and water are introduced into the chamber of the tubular atomic layer deposition equipment at the same time, the pulse time is set to 5s-10s, the purge time is set to 10s-15s, the process flow rate is set to 20sccm-25sccm, and the number of cycles of this process is 30-40 times. Thus, by setting the above parameters within a specific range, the thickness of the prepared anti-ultraviolet aluminum oxide film layer can be within the range of 4nm-6nm, and the uniformity within the sheet, between sheets and between tubes is less than or equal to 10%, respectively, thereby improving the anti-ultraviolet effect of the battery.
[0074] Exemplarily, the pulse time may be 5s, 6s, 7s, 8s, 9s, 10s, etc., or may be a range consisting of any of the above values.
[0075] Exemplarily, the purge time may be 10 s, 11 s, 12 s, 13 s, 14 s, 15 s, etc., or may be a range consisting of any of the above values.
[0076] Illustratively, the process flow rate may be 20 sccm, 21 sccm, 22 sccm, 23 sccm, 24 sccm, 25 sccm, etc., or may be a range consisting of any of the above values.
[0077] Illustratively, the number of cycles can be 30 times, 32 times, 34 times, 36 times, 38 times, 40 times, etc., or can be a range consisting of any of the above values.
[0078] In some embodiments of the present application, nitrogen (N2) is used as a carrier gas to transport the reaction precursors into the reaction chamber during the tubular atomic layer deposition process. As an inert gas, nitrogen can safely carry these reaction precursors while reducing their decomposition or reaction during the transportation process. The reaction precursors are water and / or trimethylaluminum.
[0079] In some embodiments of the present application, during the tubular atomic layer deposition process, SPC control is performed to achieve a single-cycle aluminum oxide film thickness of 0.12nm-0.14nm and a refractive index of 1.62-1.68. Exemplarily, the single-cycle aluminum oxide film thickness may be 0.12nm, 0.13nm, 0.14nm, 0.15nm, etc., or may be a range of any of the above values; the refractive index may be 1.62, 1.63, 1.64, 1.65, 1.66, 1.67, 1.68, etc., or may be a range of any of the above values.
[0080] It should be noted that the "SPC control" described in this application refers to statistical process control (SPC for short, full name Statistical Process Control), which is a process control tool that uses mathematical statistics methods. It analyzes and evaluates the production process, promptly discovers signs of systematic factors based on feedback information, and takes measures to eliminate their influence, so that the process is maintained in a controlled state affected only by random factors, in order to achieve the purpose of quality control. The "single-cycle aluminum oxide film thickness" described in this application refers to the thickness of the aluminum oxide film layer deposited on the substrate after completing a complete reaction cycle. For example, after completing the first deposition stage, the thickness of the aluminum oxide film layer deposited on the substrate is 0.12nm, 0.13nm, 0.14nm, 0.15nm, etc.
[0081] In some embodiments of the present application, after the anti-ultraviolet aluminum oxide film layer is prepared by tubular atomic layer deposition, a step of preparing a silicon nitride layer on a surface of the anti-ultraviolet aluminum oxide film layer is further included. The silicon-nitrogen ratio of the silicon nitride layer is set to 1: (3-5), and the refractive index of the prepared silicon nitride layer is 2.25-2.55. In this way, the UV resistance and passivation performance of the battery can be further improved, and the chemical structure changes of the SiNx layer caused by ultraviolet light, such as the breakage of the Si-H bond, which leads to a decrease in the passivation effect.
[0082] In some embodiments of the present application, the anti-ultraviolet aluminum oxide film layer is prepared by plate-type atomic layer deposition, referring to Figure 2 , the steps include:
[0083] S400: Setting the chamber temperature of a plate-type atomic layer deposition system
[0084] In this process, the chamber temperature of the plate-type atomic layer deposition device is set to 250° C.-290° C. For example, it can be 250° C., 260° C., 270° C., 280° C., 290° C., etc., or can be a range of any of the above values. In this way, the formation of the UV-resistant aluminum oxide film layer can be promoted.
[0085] In some embodiments of the present application, the plate-type atomic layer deposition device may be an ideal atomic layer deposition device.
[0086] S500: introducing trimethylaluminum and water into the cavity simultaneously
[0087] In this process, trimethylaluminum and water are introduced into the chamber of the plate-type atomic layer deposition equipment at the same time, wherein the flow rate of water is 2000sccm-2300sccm, the flow rate of trimethylaluminum is 2200sccm-2400sccm, the pressure is 2mbar-4mbar, and the number of cycles of this process is 8-12 times. Thus, by setting the above parameters in a specific range, the thickness of the prepared aluminum oxide film layer can be within the range of 8nm-15nm, and the uniformity within the sheet, between sheets and between tubes is less than or equal to 10%, respectively, thereby improving the anti-ultraviolet effect.
[0088] Illustratively, the water flow rate may be 2000 sccm, 2050 sccm, 2100 sccm, 2150 sccm, 2200 sccm, 2250 sccm, 2300 sccm, etc., or may be a range consisting of any of the above values.
[0089] Illustratively, the flow rate of trimethylaluminum is 2200 sccm, 2250 sccm, 2300 sccm, 2350 sccm, 2400 sccm, etc., or can be a range consisting of any of the above values.
[0090] Illustratively, the number of cycles can be 8 times, 9 times, 10 times, 11 times, 12 times, etc., or can be a range consisting of any of the above values.
[0091] In some embodiments of the present application, after the anti-ultraviolet aluminum oxide film layer is prepared by plate-type atomic layer deposition, a step of preparing a silicon nitride layer on a surface of the anti-ultraviolet aluminum oxide film layer is further included. The silicon-nitrogen ratio of the silicon nitride layer is set to 1: (3-5), and the refractive index of the prepared silicon nitride layer is set to 2.25-2.55. In this way, the UV resistance and passivation performance of the battery can be further improved, and the chemical structure changes of the SiNx layer caused by ultraviolet light, such as the breakage of the Si-H bond, which leads to a decrease in the passivation effect.
[0092] In some embodiments of the present application, the anti-ultraviolet aluminum oxide film layer is first prepared by atomic layer deposition to obtain a first aluminum oxide film layer, and then a second aluminum oxide film layer is prepared by chemical vapor deposition on a surface of the first aluminum oxide film layer. Thus, the anti-ultraviolet aluminum oxide film layer prepared by this method can have good uniformity, compactness and passivation, as well as anti-ultraviolet performance.
[0093] In some embodiments of the present application, reference Figure 3 , the atomic layer deposition step comprises:
[0094] S600: Setting the chamber temperature of the atomic layer deposition equipment
[0095] In this process, the chamber temperature of the atomic layer deposition equipment is set to 260° C.-290° C. For example, it can be 260° C., 270° C., 280° C., 290° C., etc., or can be a range of any of the above values. This can promote the formation of the first aluminum oxide film layer.
[0096] S601: Water is introduced into the cavity
[0097] In this process, water is introduced into the cavity of the atomic layer deposition equipment, and the water flow rate is set to 600sccm-1500sccm, the pressure is set to 1500mtorr-2000mtorr, and the introduction time is 5s-15s. Thus, by setting the above parameters within a specific range, the thickness of the first aluminum oxide film layer prepared by atomic layer deposition can be controlled to be greater than or equal to 4nm, and the uniformity within the sheet, between the sheets, and between the tubes are less than or equal to 10%, respectively, so that the prepared anti-ultraviolet aluminum oxide has good uniformity, density and passivation, and can improve the anti-ultraviolet performance.
[0098] Illustratively, the water flow rate is 600 sccm, 800 sccm, 1000 sccm, 1200 sccm, 1400 sccm, 1500 sccm, etc., or can be a range consisting of any of the above values.
[0099] Illustratively, the pressure is 1500 mtorr, 1600 mtorr, 1700 mtorr, 1800 mtorr, 1900 mtorr, 2000 mtorr, etc., or can be a range consisting of any of the above values.
[0100] Exemplarily, the introduction time is 5s, 7s, 9s, 11s, 13s, 15s, etc., or can be a range consisting of any of the above values.
[0101] S602: First purge
[0102] In this process, the first purge time is 20s-30s, for example, 20s, 22s, 24s, 26s, 28s, 30s, etc., or can be a range consisting of any of the above values.
[0103] S603: First vacuuming
[0104] In this process, the first vacuuming time is 25s-35s, for example, 25s, 27s, 30s, 32s, 34s, 35s, etc., or a range of any of the above values.
[0105] S604: introducing trimethylaluminum into the cavity
[0106] In this process, trimethylaluminum is introduced into the cavity of the atomic layer deposition equipment, and the flow rate of trimethylaluminum is set to 2300-2700sccm, the pressure is 1500mtorr-2000mtorr, and the introduction time is 10s-20s. Thus, by setting the above parameters within a specific range, the thickness of the first aluminum oxide film layer prepared by atomic layer deposition can be controlled to be greater than or equal to 4nm, and the uniformity within the sheet, between the sheets, and between the tubes are less than or equal to 10%, respectively, so that the prepared anti-ultraviolet aluminum oxide has good uniformity, density and passivation, and can improve the anti-ultraviolet performance.
[0107] S605: Second purge
[0108] In this process, the second purge time is 20s-30s, for example, 20s, 22s, 24s, 26s, 28s, 30s, etc., or can be a range consisting of any of the above values.
[0109] S606: Second vacuuming
[0110] In this process, the first vacuuming time is 25s-35s, for example, 25s, 27s, 30s, 32s, 34s, 35s, etc., or a range of any of the above values.
[0111] In some embodiments of the present application, S601 to S607 in atomic layer deposition are defined as one cycle, and the number of cycles is 10 to 15 times. For example, it can be 10 times, 11 times, 12 times, 13 times, 14 times, 15 times, etc., or it can be a range composed of any of the above numerical values. Thus, the thickness of the first aluminum oxide film layer prepared by atomic layer deposition can be controlled to be greater than or equal to 4nm, and the uniformity within the sheet, between sheets, and between tubes can be less than or equal to 10%, so that the prepared anti-ultraviolet aluminum oxide film layer has good uniformity, density, and passivation, and improves the anti-ultraviolet performance.
[0112] In some embodiments of the present application, during the atomic layer deposition process, SPC controls the single-cycle aluminum oxide film thickness to be 0.12nm-0.15nm and the refractive index to be 1.62-1.68. Exemplarily, the single-cycle aluminum oxide film thickness can be 0.12nm, 0.13nm, 0.14nm, 0.15nm, etc., or can be a range composed of any of the above numerical values; the refractive index can be 1.62, 1.63, 1.64, 1.65, 1.66, 1.67, 1.68, etc., or can be a range composed of any of the above numerical values. Thus, the thickness of the first aluminum oxide film layer prepared by atomic layer deposition can be controlled to be greater than or equal to 4nm, and the uniformity within the sheet, between sheets, and between tubes is less than or equal to 10%, respectively, so that the prepared aluminum oxide film layer has good uniformity, density, and passivation, and improves the anti-ultraviolet performance.
[0113] In some embodiments of the present application, reference Figure 4 , the chemical vapor deposition step comprises:
[0114] S700: Setting the chamber temperature of the chemical vapor deposition equipment
[0115] In this process, the chamber temperature of the chemical vapor deposition equipment is set to 240° C.-290° C. For example, it can be 240° C., 250° C., 260° C., 270° C., 280° C., 290° C., etc., or can be a range of any of the above values. This can promote the formation of the second aluminum oxide film layer.
[0116] S701: N2O and trimethylaluminum are introduced into the cavity simultaneously
[0117] In this process, N2O and trimethylaluminum are introduced into the chamber of the chemical vapor deposition equipment, wherein the flow rate of N2O is 2000sccm-5000sccm, the flow rate of trimethylaluminum is 500sccm-1500sccm, the pressure is 1500mtorr-2000mtorr, and the introduction time is 20s-40s. Thus, by setting the above parameters within a specific range, the thickness of the second aluminum oxide film layer prepared by chemical vapor deposition can be controlled to be 3-8nm, and by preparing the second aluminum oxide film layer, the overall passivation of the anti-ultraviolet aluminum oxide film layer can be better improved.
[0118] Illustratively, the flow rate of N2O may be 2000sccm, 3000sccm, 4000sccm, 5000sccm, etc., or may be a range consisting of any of the above values.
[0119] Illustratively, the flow rate of trimethylaluminum can be 500 sccm, 800 sccm, 1000 sccm, 1200 sccm, 1500 sccm, etc., or can be a range consisting of any of the above values.
[0120] Illustratively, the pressure may be 1500 mtorr, 1600 mtorr, 1700 mtorr, 1800 mtorr, 1900 mtorr, 2000 mtorr, etc., or may be a range consisting of any of the above values.
[0121] Exemplarily, the introduction time may be 20 s, 25 s, 30 s, 35 s, 40 s, etc., or may be a range consisting of any of the above values.
[0122] S702: First deposition stage
[0123] In this stage, the flow rate of N2O in the chamber of the chemical vapor deposition equipment is set to 2000sccm-5000sccm, the flow rate of trimethylaluminum is set to 500sccm-1500sccm, the pressure is set to 1500mtorr-2000mtorr, the power is set to 8000W-10000W, the pulse switch ratio is set to 1:700, and the first deposition time is set to 100s-150s. Therefore, by setting the above parameters within a specific range, the thickness of the second aluminum oxide film layer prepared by chemical vapor deposition can be controlled to be 3-8nm, which can better improve the overall passivation of the anti-ultraviolet aluminum oxide film layer.
[0124] Illustratively, the flow rate of N2O may be 2000sccm, 3000sccm, 4000sccm, 5000sccm, etc., or may be a range consisting of any of the above values.
[0125] Illustratively, the flow rate of trimethylaluminum can be 500 sccm, 800 sccm, 1000 sccm, 1200 sccm, 1500 sccm, etc., or can be a range consisting of any of the above values.
[0126] Illustratively, the pressure may be 1500 mtorr, 1600 mtorr, 1700 mtorr, 1800 mtorr, 1900 mtorr, 2000 mtorr, etc., or may be a range consisting of any of the above values.
[0127] Exemplarily, the power may be 8000W, 8500W, 9000W, 9500W, 10000W, etc., or may be a range consisting of any of the above values.
[0128] Illustratively, the first deposition time may be 100 s, 110 s, 120 s, 130 s, 140 s, 150 s, etc., or may be a range consisting of any of the above values.
[0129] In some embodiments of the present application, during processes S701 and S702, the flow rate of N2O, the flow rate of trimethylaluminum and the pressure are the same.
[0130] S703: The third vacuum
[0131] In this process, the third vacuuming time is 25s-35s, for example, 25s, 28s, 30s, 32s, 35s, etc., or a range of any of the above values.
[0132] In some embodiments of the present application, after the anti-ultraviolet aluminum oxide film layer is prepared by atomic layer deposition and chemical vapor deposition, a step of preparing a silicon nitride layer on the surface of the second aluminum oxide film layer away from the first aluminum oxide film layer is further included. The silicon-nitrogen ratio of the silicon nitride layer is set to 1: (3-5), and the refractive index of the prepared silicon nitride layer is set to 2.25-2.55. In this way, the UV resistance and passivation performance of the battery can be further improved, and the chemical structure changes of the SiNx layer caused by ultraviolet light, such as the breakage of Si-H bonds, which leads to a decrease in the passivation effect.
[0133] In some embodiments of the present application, the anti-ultraviolet aluminum oxide film layer is first prepared by plasma enhanced atomic layer deposition to obtain a third aluminum oxide film layer, and then a fourth aluminum oxide film layer is prepared by chemical vapor deposition on a surface of the third aluminum oxide film layer.
[0134] In some embodiments of the present application, reference Figure 5 , the plasma enhanced atomic layer deposition step comprises:
[0135] S800: Setting the chamber temperature of a plasma enhanced atomic layer deposition system
[0136] In this process, the chamber temperature of the plasma enhanced atomic layer deposition equipment is set to 240° C.-290° C. For example, it can be 240° C., 250° C., 260° C., 270° C., 280° C., 290° C., etc., or can be a range of any of the above values. Thereby, the formation of the third aluminum oxide film layer can be promoted.
[0137] S801: Introduce N2O and trimethylaluminum into the cavity
[0138] In this process, N2O and trimethylaluminum are introduced into the cavity of the plasma enhanced atomic layer deposition equipment, wherein the flow rate of N2O is 2000sccm-5000sccm, the flow rate of trimethylaluminum is 500sccm-2000sccm, the pressure is 1500mtorr-2000mtorr, and the introduction time is 20s-40s. Thus, by setting the above parameters within a specific range, the thickness of the third aluminum oxide film layer prepared by plasma enhanced atomic layer deposition can be controlled to be greater than or equal to 4nm, and the uniformity within the sheet, between the sheets and between the tubes is less than or equal to 10%, respectively, so that the prepared anti-ultraviolet aluminum oxide film layer has good uniformity, density and passivation, and improves the anti-ultraviolet performance.
[0139] Illustratively, the flow rate of N2O may be 2000sccm, 3000sccm, 4000sccm, 5000sccm, etc., or may be a range consisting of any of the above values.
[0140] Illustratively, the flow rate of trimethylaluminum can be 500 sccm, 800 sccm, 1000 sccm, 1500 sccm, 2000 sccm, etc., or can be a range consisting of any of the above values.
[0141] Illustratively, the pressure may be 1500 mtorr, 1600 mtorr, 1700 mtorr, 1800 mtorr, 1900 mtorr, 2000 mtorr, etc., or may be a range consisting of any of the above values.
[0142] Exemplarily, the introduction time may be 20 s, 25 s, 30 s, 35 s, 40 s, etc., or may be a range consisting of any of the above values.
[0143] S802: Second deposition stage
[0144] In this process, the flow rate of N2O in the chamber of the plasma enhanced atomic layer deposition equipment is set to 2000sccm-5000sccm, the flow rate of trimethylaluminum is 500sccm-2000sccm, the pressure is 1500mtorr-2000mtorr, the power is 3000W-5000W, the pulse switch ratio is 1:700, and the second deposition time is 10s-20s. Thus, by setting the above parameters within a specific range, the thickness of the third aluminum oxide film layer prepared by plasma enhanced atomic layer deposition can be controlled to be greater than or equal to 4nm, and the uniformity within the sheet, between the sheets and between the tubes is less than or equal to 10%, respectively, so that the prepared anti-ultraviolet aluminum oxide film has good uniformity, density and passivation, and improves the anti-ultraviolet performance.
[0145] Illustratively, the flow rate of N2O may be 2000sccm, 3000sccm, 4000sccm, 5000sccm, etc., or may be a range consisting of any of the above values.
[0146] Illustratively, the flow rate of trimethylaluminum can be 500 sccm, 800 sccm, 1000 sccm, 1500 sccm, 2000 sccm, etc., or can be a range consisting of any of the above values.
[0147] Illustratively, the pressure may be 1500 mtorr, 1600 mtorr, 1700 mtorr, 1800 mtorr, 1900 mtorr, 2000 mtorr, etc., or may be a range consisting of any of the above values.
[0148] Exemplarily, the power may be 3000W, 3500W, 4000W, 4500W, 5000W, etc., or may be a range consisting of any of the above values.
[0149] Illustratively, the second deposition time may be 10 s, 12 s, 14 s, 16 s, 18 s, 20 s, etc., or may be a range consisting of any of the above values.
[0150] In some embodiments of the present application, during processes S801 and S802, the flow rate of N2O, the flow rate of trimethylaluminum and the pressure are the same.
[0151] S803: The fourth vacuum
[0152] In this process, the fourth vacuuming time is 25s-35s, for example, 25s, 28s, 30s, 32s, 35s, etc., or a range of any of the above values.
[0153] In some embodiments of the present application, S801 to S803 in plasma enhanced atomic layer deposition is defined as a cycle, and the number of cycles is 5-10 times. For example, it can be 5 times, 6 times, 7 times, 8 times, 9 times, 10 times, etc., or it can be a range composed of any of the above values. In this way, the thickness of the third aluminum oxide film layer prepared by plasma enhanced atomic layer deposition can be controlled to be greater than or equal to 4nm, and the uniformity within the sheet, between sheets and between tubes is less than or equal to 10%, respectively, so that the prepared aluminum oxide film layer has good uniformity, density and passivation, and improves the anti-ultraviolet performance.
[0154] In some embodiments of the present application, the preparation method of the fourth aluminum oxide film layer is the same as the preparation method of the second aluminum oxide film layer, both of which are performed by chemical vapor deposition, and will not be repeated here.
[0155] In some embodiments of the present application, after the anti-ultraviolet aluminum oxide film layer is prepared by plasma enhanced atomic layer deposition and chemical vapor deposition, the step of preparing a silicon nitride layer on the surface of the fourth aluminum oxide film layer away from the third aluminum oxide film layer is further included. The silicon-nitrogen ratio of the silicon nitride layer is set to 1: (3-5), and the refractive index of the prepared silicon nitride layer is set to 2.25-2.55. In this way, the UV resistance and passivation performance of the battery can be further improved, and the chemical structure changes of the SiNx layer caused by ultraviolet light, such as the breakage of the Si-H bond, which leads to a decrease in the passivation effect.
[0156] In some embodiments of the present application, the anti-ultraviolet aluminum oxide film layer is first prepared by atomic layer deposition to obtain a fifth aluminum oxide film layer, and then a sixth aluminum oxide film layer is prepared by chemical vapor deposition on a surface of the fifth aluminum oxide film layer, and finally a seventh aluminum oxide film layer is prepared by plasma enhanced atomic layer deposition on a surface of the sixth aluminum oxide film layer away from the fifth aluminum oxide film layer. The preparation method of the fifth aluminum oxide film layer is the same as the preparation method of the first aluminum oxide film layer, both of which are prepared by atomic layer deposition; the preparation method of the sixth aluminum oxide film layer is the same as the preparation method of the second aluminum oxide film layer, both of which are prepared by chemical vapor deposition; the preparation method of the seventh aluminum oxide film layer is the same as the preparation method of the third aluminum oxide film layer, both of which are prepared by plasma enhanced atomic layer deposition.
[0157] In some embodiments of the present application, after the anti-ultraviolet aluminum oxide film layer is prepared by atomic layer deposition, chemical vapor deposition and plasma enhanced atomic layer deposition, the step of preparing a silicon nitride layer on the surface of the seventh aluminum oxide film layer away from the sixth aluminum oxide film layer is further included. The silicon-nitrogen ratio of the silicon nitride layer is set to 1: (3-5), and the refractive index of the prepared silicon nitride layer is set to 2.25-2.55. In this way, the UV resistance and passivation performance of the battery can be further improved, and the chemical structure changes of the SiNx layer caused by ultraviolet light, such as the breakage of the Si-H bond, can be reduced, resulting in a decrease in the passivation effect.
[0158] In some embodiments of the present application, the above-mentioned equipment for preparing UV-resistant aluminum oxide film layer by atomic layer deposition and chemical vapor deposition, chemical vapor deposition and plasma enhanced atomic layer deposition, or atomic layer deposition, chemical vapor deposition and plasma enhanced atomic layer deposition can be a three-in-one equipment, namely, the Jiejiachuang tubular alumina equipment.
[0159] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.
[0160] Example 1: Tubular ALD Deposition
[0161] Normal N-type Topcon cells, after texturing, boron diffusion (B diffusion) of silicon wafers, removal or cleaning of borosilicate glass (BSG removal) on the back, back polishing or back etching (back polishing), polysilicon deposition (poly deposition), annealing, de-coating, and cleaning with radioactive chemical sensitizer (RCA), begin to prepare aluminum oxide. Aluminum oxide is prepared using tubular ALD equipment similar to Microguide and Songyu. The aluminum oxide preparation process: the chamber temperature is controlled at 260°C, the process preheating time is 900s, H2O is passed in the first stage, the pulse time is 7s, the purge time is 12s, the process flow rate is 18sccm (N2 source), and the number of cycles is 5 times; in the second stage, TMA and H2O are passed at the same time, the pulse time of both is 6s, the purge time is 11s, the process flow rate is 22sccm (N2 source), and the number of cycles is 32 times; in this way, the preparation of aluminum oxide is completed after a total cycle of the first and second stages. Next, prepare the front silicon nitride film layer, where the SiH4:NH3 of the bottom silicon nitride is 1:4.5, and the other overall settings are carried out in the conventional way. After preparing the front silicon nitride, continue with the back film, screen printing, sintering, and testing to complete the preparation of the entire battery. The refractive index of aluminum oxide is 1.65, and the refractive index of the bottom silicon nitride is 2.35.
[0162] The monitoring data of alumina thickness at different positions in the same tube and the UV test results of the components are shown in Tables 1 and 2 below. It can be seen that the intra-sheet uniformity and inter-sheet uniformity of the aluminum oxide film layer obtained by the preparation method of the present application are both less than 10%, and after the prepared battery is subjected to UV aging test, the UV attenuation is reduced to within -1%.
[0163] Table 1
[0164]
[0165] Note: The mean value of the whole tube refers to the average value of all test data of 6 pieces of the whole tube; a row is the thickness value of five points tested in a piece, and the range within a piece is the maximum value minus the minimum value of the five points in a piece; uniformity within a piece = range within a piece / mean within a piece / 2; uniformity between pieces = range of all single points in the whole tube / mean of the whole tube / 2.
[0166] Furthermore, 10 tubes were taken to prepare anti-ultraviolet aluminum oxide film layers under the same conditions, and the thickness of the anti-ultraviolet aluminum oxide film layers at different positions in each tube was tested according to the above method. The results were: the maximum thickness of the anti-ultraviolet aluminum oxide film layers in the 10 tubes was 5.31 nm, and the minimum thickness was 4.86 nm. The range of thickness of all tubes was 0.45 nm, and the average thickness of the anti-ultraviolet aluminum oxide film layers of all tubes was measured to be 4.98 nm. The inter-tube uniformity of the anti-ultraviolet aluminum oxide film layer prepared by the method of this embodiment was 4.5% (inter-tube uniformity = range of all tubes / average of all tubes / 2).
[0167] Table 2
[0168]
[0169] Among them, power attenuation = Pmax before UV60 / Pmax after UV60-1.
[0170] Example 2: Tubular ALD Deposition
[0171] Normal N-type Topcon cells, after texturing, boron diffusion (B diffusion) of silicon wafers, removal or cleaning of borosilicate glass (BSG removal) on the back, back polishing or back etching (back polishing), polysilicon deposition (poly deposition), annealing, de-coating, and cleaning with radioactive chemical sensitizer (RCA), begin to prepare aluminum oxide. Aluminum oxide is prepared using tubular ALD equipment similar to Microguide and Songyu. The aluminum oxide preparation process: the chamber temperature is controlled at 270°C, the process preheating time is 1000s, H2O is passed in the first stage, the pulse time is 8s, the purge time is 14s, the process flow rate is 20sccm (N2 source), and the number of cycles is 5 times; in the second stage, TMA and H2O are passed at the same time, the pulse time of both is 7s, the purge time is 13s, the process flow rate is 24sccm (N2 source), and the number of cycles is 34 times; in this way, the preparation of aluminum oxide is completed after a total cycle of the first and second stages. Next, prepare the front silicon nitride film layer, where the SiH4:NH3 of the bottom silicon nitride is 1:3.5, and the other overall settings are carried out in the conventional way. After preparing the front silicon nitride, continue with the back film, screen printing, sintering, and testing to complete the preparation of the entire battery. The refractive index of aluminum oxide is 1.64, and the refractive index of the bottom silicon nitride is 2.42.
[0172] The monitoring data of alumina thickness at different positions in the same tube and the UV test results of the components are shown in Tables 3 and 4. It can be seen that the intra-sheet uniformity and inter-sheet uniformity of the aluminum oxide film layer obtained by the preparation method of the present application are both less than 10%, and after the prepared battery is subjected to UV aging test, the UV attenuation is reduced to within -1%.
[0173] Table 3
[0174]
[0175] Furthermore, 10 tubes were taken to prepare anti-ultraviolet aluminum oxide film layers under the same conditions, and the thickness of the anti-ultraviolet aluminum oxide film layers at different positions in each tube was tested according to the above method. The results were: the maximum thickness of the anti-ultraviolet aluminum oxide film layers in the 10 tubes was 5.42nm, and the minimum thickness was 5.09nm. The thickness range of all tubes was 0.33nm, and the average thickness of the anti-ultraviolet aluminum oxide film layers of all tubes was measured to be 5.28nm. The inter-tube uniformity of the anti-ultraviolet aluminum oxide film layer prepared by the method of this embodiment was 3.1%.
[0176] Table 4
[0177]
[0178] Example 3: Plate ALD deposition
[0179] Normal N-type Topcon cells, after texturing, boron diffusion (B diffusion) of silicon wafers, removal or cleaning of the back borosilicate glass (BSG removal), back polishing or back etching (back polishing), polysilicon deposition (poly deposition), annealing, de-coating, and cleaning with radioactive chemical sensitizer (RCA), begin to prepare aluminum oxide. Ideal ALD equipment is used to prepare aluminum oxide. The aluminum oxide preparation process: the chamber temperature is controlled at 260°C, the H2O flow rate is 2100sccm, the TMA flow rate is 2300sccm, the pressure is 3mbar, and the number of loops is 4+4 times (4 times in each chamber, a total of 2 chambers). Next, prepare the front silicon nitride film layer, in which the SiH4:NH3 of the bottom silicon nitride is 1:4.5, and the other overall settings are carried out in the conventional manner. After the preparation of the front silicon nitride, continue with the back film, screen printing, sintering, and testing to complete the preparation of the entire battery. The refractive index of the bottom silicon nitride is 2.35.
[0180] The alumina thickness monitoring data of the sample sheets at different positions in the same carrier and the component UV test results are shown in Tables 5 and 6. It can be seen that the intra-sheet uniformity and inter-sheet uniformity of the aluminum oxide film layer obtained by the preparation method of the present application are both less than 10%, and after the prepared battery is subjected to UV aging test, the UV attenuation is reduced to within -1%.
[0181] Table 5
[0182]
[0183] Furthermore, 10 tubes were taken to prepare anti-ultraviolet aluminum oxide film layers under the same conditions, and the thickness of the anti-ultraviolet aluminum oxide film layers at different positions in each tube was tested according to the above method. The results were: the maximum thickness of the anti-ultraviolet aluminum oxide film layers in the 10 tubes was 10.95nm, and the minimum thickness was 10.43nm. The thickness range of all tubes was 0.52nm, and the average thickness of the anti-ultraviolet aluminum oxide film layers of all tubes was measured to be 10.62nm. The inter-tube uniformity of the anti-ultraviolet aluminum oxide film layer prepared by the method of this embodiment was 2.4%.
[0184] Table 6
[0185]
[0186] Example 4: Plate ALD deposition
[0187] Normal N-type Topcon cells, after texturing, boron diffusion (B diffusion) of silicon wafers, removal or cleaning of the back borosilicate glass (BSG removal), back polishing or back etching (back polishing), polysilicon deposition (poly deposition), annealing, de-coating, and cleaning with radioactive chemical sensitizer (RCA), begin to prepare aluminum oxide. Ideal ALD equipment is used to prepare aluminum oxide. The aluminum oxide preparation process: the chamber temperature is controlled at 270°C, the H2O flow rate is 2000sccm, the TMA flow rate is 2200sccm, the pressure is 4mbar, and the number of loops is 3+5 times (3 times in one chamber and 5 times in one chamber). Next, the front silicon nitride film layer is prepared, in which the SiH4:NH3 of the bottom silicon nitride is 1:3.5, and the other overall settings are carried out in the conventional manner. After the preparation of the front silicon nitride, the back film, screen printing, sintering, and testing are continued to complete the preparation of the entire battery. The refractive index of the bottom silicon nitride is 2.42.
[0188] The alumina thickness monitoring data of the sample sheets at different positions in the same carrier and the component UV test results are shown in Tables 7 and 8. It can be seen that the intra-sheet uniformity and inter-sheet uniformity of the aluminum oxide film layer obtained by the preparation method of the present application are both less than 10%, and after the prepared battery is subjected to UV aging test, the UV attenuation is reduced to within -1%.
[0189] Table 7
[0190]
[0191] Furthermore, 10 tubes were taken to prepare anti-ultraviolet aluminum oxide film layers under the same conditions, and the thickness of the anti-ultraviolet aluminum oxide film layers at different positions in each tube was tested according to the above method. The results were: the maximum thickness of the anti-ultraviolet aluminum oxide film layers in the 10 tubes was 11.25nm, and the minimum thickness was 10.46nm. The thickness range of all tubes was 0.59nm, and the average thickness of the anti-ultraviolet aluminum oxide film layers of all tubes was measured to be 10.70nm. The inter-tube uniformity of the anti-ultraviolet aluminum oxide film layer prepared by the method of this embodiment was 2.7%.
[0192] Table 8
[0193]
[0194]
[0195] Example 5: ALD+CVD+PEALD deposition
[0196] A normal N-type Topcon cell undergoes texturing, boron diffusion (B diffusion) of the silicon wafer, removal or cleaning of the borosilicate glass on the back (BSG removal), back polishing or back etching (back polishing), polysilicon deposition (poly deposition), annealing, de-coating, and cleaning with a radioactive chemical sensitizer (RCA), and then begins to prepare alumina.
[0197] Alumina is prepared using Jiejia Chuang's three-in-one alumina preparation equipment. Alumina preparation process:
[0198] For the ALD layer, the chamber temperature was controlled at 260°C. First, H2O was passed: flow rate 800sccm, pressure 1700mtorr, time 10s, purge: time 25s, vacuum: time 30s. TMA flow rate 2500sccm, pressure 1700mtorr, time 15s, purge: time 25s, vacuum: time 30s. "H2O passed-purge-vacuum-pass TMA-purge-vacuum" is one small cycle, and 12 small cycles are repeated.
[0199] CVD layer, the chamber temperature is controlled at 260℃, pre-ventilation: N2O flow rate 2500sccm, TMA flow rate 800sccm, pressure 1800mtorr, time 25s, CVD deposition step: N2O flow rate 2500sccm, TMA flow rate 800sccm, pressure 1800mtorr, power 8500W, pulse on / off ratio 40:2800, time 100s, vacuum pumping: time 30s;
[0200] For the PEALD layer, the chamber temperature is controlled at 260°C. Pre-ventilation: N2O flow rate 2800sccm, TMA flow rate 1800sccm, pressure 1700mtorr, time 30s; PEALD deposition: N2O flow rate 2800sccm, TMA flow rate 1800sccm, pressure 1700mtorr, power 4000W, pulse switch ratio 20:1400, time 15s, vacuumization, time 30s; "pre-ventilation-PEALD deposition-vacuumization" is a small cycle, and this is repeated for 6 small cycles.
[0201] Next, prepare the front silicon nitride film layer, where the SiH4:NH3 of the bottom silicon nitride is 1:4.5, and the other overall settings are carried out in the conventional way. After preparing the front silicon nitride, continue with the back film, screen printing, sintering, and testing to complete the preparation of the entire battery. The refractive index of the bottom silicon nitride is 2.35.
[0202] The monitoring data of alumina thickness at different positions in the same tube and the UV test results of the components are shown in Tables 9 and 10. It can be seen that the intra-sheet uniformity and inter-sheet uniformity of the aluminum oxide film layer obtained by the preparation method of the present application are both less than 10%, and after the prepared battery is subjected to UV aging test, the UV attenuation is reduced to within -1%.
[0203] Table 9
[0204]
[0205]
[0206] Further, 10 tubes were prepared with anti-ultraviolet aluminum oxide films under the same conditions, and the thickness of the anti-ultraviolet aluminum oxide films at different positions in each tube was tested according to the above method. The results were as follows: the maximum thickness of the anti-ultraviolet aluminum oxide films in the 10 tubes was 8.05 nm, and the minimum thickness was 7.32 nm, so the thickness range of all tubes was 0.73 nm, and the average thickness of the anti-ultraviolet aluminum oxide films of all tubes was 7.76 nm, so the inter-tube uniformity of the anti-ultraviolet aluminum oxide films prepared by the method of this embodiment was 4.7%.
[0207] Table 10
[0208]
[0209] Comparative Example 1
[0210] Normal N-type Topcon cells, after texturing, boron diffusion (B diffusion) of silicon wafers, removal or cleaning of the borosilicate glass on the back (removal of BSG), back polishing or back etching (back polishing), polysilicon deposition (poly deposition), annealing, de-coating, and cleaning with radioactive chemical sensitizer (RCA), begin to prepare aluminum oxide. Aluminum oxide is prepared using tubular ALD equipment similar to Microguide and Songyu. The aluminum oxide preparation process: the chamber temperature is controlled at 250°C, the process preheating time is 850s, H2O is passed in the first stage, the pulse time is 6s, the purge time is 10s, the process flow rate is 18sccm (N2 source), and the number of cycles is 5 times; in the second stage, TMA and H2O are passed at the same time, the pulse time of both is 4s, the purge time is 8s, the process flow rate is 18sccm (N2 source), and the number of cycles is 30 times; in this way, the preparation of aluminum oxide is completed after a total cycle of the first and second stages. Next, prepare the front silicon nitride film layer, where the SiH4:NH3 of the bottom silicon nitride is 1:5.3, and the other overall settings are carried out in the conventional way. After preparing the front silicon nitride, continue with the back film, screen printing, sintering, and testing to complete the preparation of the entire battery. The refractive index of aluminum oxide is 1.76, and the refractive index of the bottom silicon nitride is 2.26.
[0211] The monitoring data of alumina thickness at different positions in the same tube and the UV test results of the components are shown in Tables 11 and 12 below. It can be seen that although the intra-sheet uniformity and inter-sheet uniformity of the alumina film layer obtained by the preparation method of this process are both less than 10%, after the prepared battery is subjected to UV aging test, the UV attenuation is much greater than -1%.
[0212] Table 11
[0213]
[0214]
[0215] Table 12
[0216]
[0217] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0218] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A tunneling oxide passivation contact solar cell, characterized in that: The tunneling oxidation passivation contact solar cell comprises an anti-ultraviolet aluminum oxide film layer, the thickness of the anti-ultraviolet aluminum oxide film layer is 4nm-20nm, and the thickness uniformity is less than or equal to 10%.
2. The battery according to claim 1, characterized in that The anti-ultraviolet aluminum oxide film layer is prepared by tubular atomic layer deposition, and the thickness of the anti-ultraviolet aluminum oxide film layer is 4nm-6nm.
3. The battery according to claim 1, characterized in that The anti-ultraviolet aluminum oxide film layer is prepared by plate-type atomic layer deposition, and the thickness of the anti-ultraviolet aluminum oxide film layer is 8nm-15nm.
4. The battery according to claim 1, characterized in that The anti-ultraviolet aluminum oxide film layer meets one of the following conditions: A. The anti-ultraviolet aluminum oxide film layer comprises a first aluminum oxide film layer and a second aluminum oxide film layer stacked in sequence, wherein the first aluminum oxide film layer is prepared by atomic layer deposition, and the second aluminum oxide film layer is prepared by chemical vapor deposition, wherein the thickness of the first aluminum oxide film layer is greater than or equal to 4 nm, and the thickness of the second aluminum oxide film layer is 3 nm-8 nm; B. The anti-ultraviolet aluminum oxide film layer comprises a third aluminum oxide film layer and a fourth aluminum oxide film layer stacked in sequence, wherein the third aluminum oxide film layer is prepared by plasma enhanced atomic layer deposition, and the fourth aluminum oxide film layer is prepared by chemical vapor deposition, and the thickness of the third aluminum oxide film layer is greater than or equal to 4 nm, and the thickness of the fourth aluminum oxide film layer is 3 nm-8 nm; C. The anti-ultraviolet aluminum oxide film layer includes a fifth aluminum oxide film layer, a sixth aluminum oxide film layer and a seventh aluminum oxide film layer which are stacked in sequence, the fifth aluminum oxide film layer is prepared by the atomic layer deposition, the sixth aluminum oxide film layer is prepared by the chemical vapor deposition, the seventh aluminum oxide film layer is prepared by the plasma enhanced atomic layer deposition, the thickness of the fifth aluminum oxide film layer is 1nm-3nm, the thickness of the sixth aluminum oxide film layer is 3nm-8nm, the thickness of the seventh aluminum oxide film layer is 1nm-5nm, and the sum of the thicknesses of the fifth aluminum oxide film layer and the seventh aluminum oxide film layer is greater than or equal to 4nm.
5. The battery according to any one of claims 1 to 4, characterized in that: The refractive index of the anti-ultraviolet aluminum oxide film layer prepared by the atomic layer deposition or the plasma enhanced atomic layer deposition is 1.62 to 1.
68.
6. The battery according to any one of claims 1 to 5, characterized in that: The battery further includes a silicon nitride layer, which is disposed on a surface of the anti-ultraviolet aluminum oxide film layer, wherein the silicon nitride layer satisfies at least one of the following conditions: The silicon-nitrogen ratio in the silicon nitride layer is 1:(3-5); The refractive index of the silicon nitride layer is 2.25-2.
55.
7. A method for preparing a tunneling oxide passivated contact solar cell according to any one of claims 1 to 6, characterized in that: The method comprises the step of preparing an anti-ultraviolet aluminum oxide film layer, and the method of preparing the anti-ultraviolet aluminum oxide film layer comprises atomic layer deposition.
8. The method according to claim 7, characterized in that The anti-ultraviolet aluminum oxide film layer is prepared by tubular atomic layer deposition, and the steps include: 1) Set the chamber temperature of the tubular atomic layer deposition equipment to 260°C-290°C and the process preheating time to 800s-1000s; 2) Water is introduced into the chamber. During this process, the pulse time is 5s-10s, the purge time is 10s-15s, the process flow rate is 15sccm-20sccm, and the number of cycles of this process is 3-7 times; 3) Trimethylaluminum and water are introduced into the chamber simultaneously. In this process, the pulse time is 5s-10s, the purge time is 10s-15s, the process flow rate is 20sccm-25sccm, and the number of cycles of this process is 30-40 times.
9. The method according to claim 7, characterized in that: The anti-ultraviolet aluminum oxide film layer is prepared by plate-type atomic layer deposition, and the steps include: setting the chamber temperature of the plate-type atomic layer deposition equipment to 250°C-290°C, and simultaneously introducing trimethylaluminum and water into the chamber. During the process, the flow rate of the trimethylaluminum is 2200sccm-2400sccm, the flow rate of the water is 2000sccm-2300sccm, the pressure is 2mbar-4mbar, and the number of cycles of the process is 8-12 times.
10. The method according to claim 7, characterized in that The anti-ultraviolet aluminum oxide film layer is prepared by one of the following methods: A. Firstly, a first aluminum oxide film layer is prepared by atomic layer deposition, and then a second aluminum oxide film layer is prepared by chemical vapor deposition on a surface of the first aluminum oxide film layer, wherein: The atomic layer deposition step comprises: 1) Set the chamber temperature of the atomic layer deposition equipment to 260°C-290°C; 2) introducing water into the cavity. During the process, the water flow rate is 600sccm-1500sccm, the pressure is 1500mtorr-2000mtorr, and the introduction time is 5s-15s; 3) a first purge, wherein the time of the first purge is 20s-30s; 4) first vacuuming, wherein the time of the first vacuuming is 25s-35s; 5) introducing trimethylaluminum into the chamber, wherein the flow rate of the trimethylaluminum is 2300sccm-2700sccm, the pressure is 1500mtorr-2000mtorr, and the introduction time is 10s-20s; 6) Second purge, the second purge time is 20s-30s; 7) second vacuuming, the second vacuuming time is 25s-35s; The atomic layer deposition step 2) to step 7) is defined as a cycle, and the number of cycles is 10-15 times; The chemical vapor deposition step comprises: 1) Set the chamber temperature of the chemical vapor deposition equipment to 240°C-290°C; 2) introducing N2O and trimethylaluminum into the chamber simultaneously, during which the flow rate of N2O is 2000sccm-5000sccm, the flow rate of trimethylaluminum is 500sccm-1500sccm, the pressure is 1500mtorr-2000mtorr, and the introduction time is 20s-40s; 3) The first deposition stage, during which the flow rate of N2O is 2000sccm-5000sccm, the flow rate of trimethylaluminum is 500sccm-1500sccm, the pressure is 1500mtorr-2000mtorr, the power is 8000W-10000W, the pulse on / off ratio is 1:700, and the first deposition time is 100s-150s; 4) a third vacuuming step, wherein the third vacuuming step lasts for 25s to 35s; B. Firstly, a third aluminum oxide film layer is prepared by plasma enhanced atomic layer deposition, and then a fourth aluminum oxide film layer is prepared by chemical vapor deposition on a surface of the third aluminum oxide film layer, wherein: The plasma enhanced atomic layer deposition step comprises: 1) Setting the chamber temperature of the plasma enhanced atomic layer deposition equipment to 240°C-290°C; 2) introducing N2O and trimethylaluminum into the chamber. In this process, the flow rate of N2O is 2000sccm-5000sccm, the flow rate of trimethylaluminum is 500sccm-2000sccm, the pressure is 1500mtorr-2000mtorr, and the introduction time is 20s-40s; 3) A second deposition stage, during which the flow rate of N2O is 2000sccm-5000sccm, the flow rate of trimethylaluminum is 500sccm-2000sccm, the pressure is 1500mtorr-2000mtorr, the power is 3000W-5000W, the pulse on / off ratio is 1:700, and the second deposition time is 10s-20s; 4) a fourth vacuuming step, wherein the fourth vacuuming step lasts for 25 s to 35 s; The steps 2) to 4) of the plasma enhanced atomic layer deposition are defined as one cycle, and the number of cycles is 5 to 10 times; The chemical vapor deposition step comprises: 1) Set the chamber temperature of the chemical vapor deposition equipment to 240°C-290°C; 2) introducing N2O and trimethylaluminum into the chamber simultaneously, during which the flow rate of N2O is 2000sccm-5000sccm, the flow rate of trimethylaluminum is 500sccm-1500sccm, the pressure is 1500mtorr-2000mtorr, and the introduction time is 20s-40s; 3) The first deposition stage, during which the flow rate of N2O is 2000sccm-5000sccm, the flow rate of trimethylaluminum is 500sccm-1500sccm, the pressure is 1500mtorr-2000mtorr, the power is 8000W-10000W, the pulse on / off ratio is 1:700, and the first deposition time is 100s-150s; 4) a third vacuuming step, wherein the third vacuuming step lasts for 25s to 35s; C. Firstly, a fifth aluminum oxide film layer is prepared by atomic layer deposition, and then a sixth aluminum oxide film layer is prepared by chemical vapor deposition on a surface of the fifth aluminum oxide film layer, and finally, a seventh aluminum oxide film layer is prepared by plasma enhanced atomic layer deposition on a surface of the sixth aluminum oxide film layer away from the fifth aluminum oxide film layer, wherein: The atomic layer deposition step comprises: 1) Set the chamber temperature of the atomic layer deposition equipment to 260-290°C; 2) introducing water into the cavity. During the process, the water flow rate is 600sccm-1500sccm, the pressure is 1500mtorr-2000mtorr, and the introduction time is 5s-15s; 3) a first purge, wherein the time of the first purge is 20s-30s; 4) first vacuuming, wherein the time of the first vacuuming is 25s-35s; 5) introducing trimethylaluminum into the chamber, wherein the flow rate of the trimethylaluminum is 2300sccm-2700sccm, the pressure is 1500mtorr-2000mtorr, and the introduction time is 10s-20s; 6) Second purge, the second purge time is 20s-30s 7) second vacuuming, the second vacuuming time is 25s-35s; The atomic layer deposition step 2) to step 7) is defined as a cycle, and the number of cycles is 10-15 times; The chemical vapor deposition step comprises: 1) Set the chamber temperature of the chemical vapor deposition equipment to 240°C-290°C; 2) introducing N2O and trimethylaluminum into the chamber simultaneously, during which the flow rate of N2O is 2000sccm-5000sccm, the flow rate of trimethylaluminum is 500sccm-1500sccm, the pressure is 1500mtorr-2000mtorr, and the introduction time is 20s-40s; 3) The first deposition stage, during which the flow rate of N2O is 2000sccm-5000sccm, the flow rate of trimethylaluminum is 500sccm-1500sccm, the pressure is 1500mtorr-2000mtorr, the power is 8000W-10000W, the pulse on / off ratio is 1:700, and the first deposition time is 100s-150s; 4) a third vacuuming step, wherein the third vacuuming step lasts for 25s to 35s; The plasma enhanced atomic layer deposition step comprises: 1) Setting the chamber temperature of the plasma enhanced atomic layer deposition equipment to 240°C-290°C; 2) introducing N2O and trimethylaluminum into the chamber. In this process, the flow rate of N2O is 2000sccm-5000sccm, the flow rate of trimethylaluminum is 500sccm-2000sccm, the pressure is 1500mtorr-2000mtorr, and the introduction time is 20s-40s; 3) A second deposition stage, during which the flow rate of N2O is 2000sccm-5000sccm, the flow rate of trimethylaluminum is 500sccm-2000sccm, the pressure is 1500mtorr-2000mtorr, the power is 3000W-5000W, the pulse on / off ratio is 1:700, and the second deposition time is 10-20s; 4) a fourth vacuuming step, wherein the fourth vacuuming step lasts for 25-35 seconds; Steps 2) to 4) of the plasma enhanced atomic layer deposition are defined as one cycle, and the number of cycles is 5 to 10 times.
11. The method according to any one of claims 7 to 10, characterized in that: The method also includes the step of preparing a silicon nitride layer on a surface of the anti-ultraviolet aluminum oxide film layer.